Selecting and Retaining Friends on the Basis of Cigarette Smoking Similarity. (19th August 2013) - DeLay, Dawn; Laursen, Brett; Kiuru, Noona; Salmela‐Aro, Katariina; Nurmi, Jari‐Erik
<x xml:space="preserve">Abstract</x> This study examines whether friend selection, deselection, and socialization differ as a function of the level of cigarette smoking in the friendship group. A total of 1419 students (median age = 16) from upper secondary and vocational schools in Finland were included as targets in the peer network. Targets in the peer network were asked to nominate friends and describe their own cigarette smoking at two time points one year apart. Network analyses revealed similarity arising from selection and deselection on the basis of smoking. Selection effects (i.e., selecting new friends based on similarity) were stronger for adolescents in low‐smoking groups. Deselection effects (i.e., dropping friends based on dissimilarity) were stronger for adolescents in high‐smoking groups.